2022
DOI: 10.1172/jci153397
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor signaling promotes Treg suppressive function during allergic airway inflammation

Abstract: Women have higher prevalence of asthma compared to men. In asthma, allergic airway inflammation is initiated by IL-33 signaling through ST2, leading to increased IL-4, IL-5, and IL-13 production and eosinophil infiltration. Foxp3+ Tregs suppress and ST2+ Tregs promote allergic airway inflammation. Clinical studies showed the androgen, dehydroepiandrosterone (DHEA), reduced asthma symptoms in patients, and mouse studies showed androgen receptor (AR) signaling decreased allergic airway inflammation. Yet, the rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 78 publications
(109 reference statements)
1
33
0
2
Order By: Relevance
“…AR signalling induced by androgens stabilizes CD4 + regulatory T cells (Tregs) suppressive function, providing a mechanism for higher prevalence of asthma in women compared with men [ 64 ]. This evidence is supported by the fact that the higher airway expression of AR and higher androgen levels in men are associated with better lung function, fewer symptoms, and a lower fraction exhaled nitric oxide (FeNO) in asthma [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…AR signalling induced by androgens stabilizes CD4 + regulatory T cells (Tregs) suppressive function, providing a mechanism for higher prevalence of asthma in women compared with men [ 64 ]. This evidence is supported by the fact that the higher airway expression of AR and higher androgen levels in men are associated with better lung function, fewer symptoms, and a lower fraction exhaled nitric oxide (FeNO) in asthma [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent longitudinal study throughout adolescence found that asthma severity decreased equally in male and female subjects, probably due to increase in androgens in both sexes 47 . Androgen levels were found to be positively associated with increased pulmonary function 18,88 , as well as suppression of airway inflammation 89,90 . Due to the demographics of our cohort, we captured late pubertal stages in females, which are associated with increased incidence of asthma 14 , thus resulting in the sex-specific patterns of gene expression that we observed.…”
Section: Discussionmentioning
confidence: 97%
“…In previous study, the estrogen is associated with the elevation of interleukins and reactive oxygen species 30 . Besides, the relationship between androgen and the suppression of inflammatory reaction had been established 31 , 32 . However, there was no strong correlation between the androgen deficiency and the autoimmune disease, which indicated that the elevation of inflammatory process is not always cause inflammation-related disease.…”
Section: Discussionmentioning
confidence: 99%